2023
DOI: 10.1056/nejmoa2208822
|View full text |Cite
|
Sign up to set email alerts
|

VV116 versus Nirmatrelvir–Ritonavir for Oral Treatment of Covid-19

Abstract: Background Nirmatrelvir–ritonavir has been authorized for emergency use by many countries for the treatment of coronavirus disease 2019 (Covid-19). However, the supply falls short of the global demand, which creates a need for more options. VV116 is an oral antiviral agent with potent activity against severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Methods We conducted a phase 3, noninferiority, observer-blinded, randomized trial during the outbreak caused… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
117
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 146 publications
(119 citation statements)
references
References 25 publications
(27 reference statements)
2
117
0
Order By: Relevance
“…Nirmatrelvir/ritonavir and VV116, a remdesivir derivative, were included as new oral small-molecule antiviral drugs in our study; the former has an emergency use authorization from the US Food and Drug Administration [ 22 ], while the latter is currently undergoing clinical trials [ 15 , 23 , 24 ]. Ideally, the evaluation of protease inhibition for COVID-19 in high-risk patients (EPIC-HR) trial conducted by Hammond et al showed that early treatment with nirmatrelvir/ritonavir could significantly reduce both the viral load and risk of COVID-19-related hospitalization or death [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nirmatrelvir/ritonavir and VV116, a remdesivir derivative, were included as new oral small-molecule antiviral drugs in our study; the former has an emergency use authorization from the US Food and Drug Administration [ 22 ], while the latter is currently undergoing clinical trials [ 15 , 23 , 24 ]. Ideally, the evaluation of protease inhibition for COVID-19 in high-risk patients (EPIC-HR) trial conducted by Hammond et al showed that early treatment with nirmatrelvir/ritonavir could significantly reduce both the viral load and risk of COVID-19-related hospitalization or death [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…The drug had shown its potential against COVID-19 as it reduces lethality by 89%. It has been shown that treatment with nirmatrelvir–ritonavir reduces the risk of hospitalization or progression to severe COVID-19 infection in vaccinated patients with COVID-19 ( Cao et al, 2022 ). The safety profile of nirmatrelvir is promising, as it has mild side effects and does not have dose-dependent toxicity.…”
Section: Antivirals For the Treatment Of Covid-19mentioning
confidence: 99%
“…Both molnupiravir and ritonavir/nirmatrelvir have shown to reduce the risk for severe COVID-19, including hospitalization and/or death, compared with placebo in unvaccinated individuals [ 11 , 12 ]. More recent data including vaccinated patients with mild COVID-19 support the early administration of antivirals for preventing severe outcomes [ 13 ]. Although available evidence supports the use of antivirals in patients with SARS-CoV-2 infection to prevent severe disease, relevant data on MM patients are scarce.…”
Section: Introductionmentioning
confidence: 99%